THE IMPACT OF COMPLAINING ON THE HEALING PROCESS: PSYCHOLOGICAL, MEDICAL, AND ISLAMIC SPIRITUAL PERSPECTIVES - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti, Novariza (PT. Jurnal Center Indonesia Publisher, 2025)
Complaining is a common emotional response to illness, yet its impact on healing is rarely examined from a multidisciplinary perspective. This article aims to analyze how complaining influences the recovery process through psychological, Islamic spiritual, and medical lenses. The method used was a literature review with a descriptive qualitative approach. Data were collected from scientific articles published between 2015 and 2024 using Scopus, PubMed, DOAJ, and Google Scholar. Findings reveal that excessive complaining amplifies stress, worsens mental health, and disrupts the immune system. Psychologically, uncontrolled complaints are linked to low emotional resilience. From an Islamic view, patience (shabr) and supplication to God provide spiritual strength and mental stability. Medically, emotional stress raises cortisol levels, negatively impacting tissue healing and immune responses. This study underscores the urgency of a holistic approach that integrates psychological, spiritual, and medical dimensions in healthcare services. It contributes to scientific discourse by offering a model for more humane and comprehensive healthcare. Further empirical studies are recommended to validate this integration in clinical settings.